Original paperThe influence of corticosteroid treatment on the OPG/RANK/RANKL pathway and osteocalcin in patients with pemphigus - Chmielnicka, Marlena; Woźniacka, Anna; Torzecka, Jolanta D. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: Pemphigus is a rare autoimmune blistering disease, which requires prolonged administration of corticosteroids at high doses. Although this therapy improves the health and lives of patients, it may have various side effects, for example osteoporosis. Aim: To assess the concentration of osteoprotegerin (OPG), the soluble receptor activator of nuclear factor-κβ ligand (sRANKL) and osteocalcin in patients with pemphigus. Material and methods : The study comprised a group of 29 patients with pemphigus (17 women and 12 men) aged between 23 years and 75 years treated from 1994 to 2009 in the Department of Dermatology and Venereology, Medical University of Lodz, as well as 24 healthy volunteers matched appropriately in terms of gender and age. Results : In patients with pemphigus, the mean osteoprotegerin concentration was up to 16.46% higher than in the control group. The average RANKL concentration in serum of patients with pemphigus was 26.88% higher. However, the patient group demonstrated a significantly lower concentration of osteocalcin by up to 18.03%. Conclusions : Under corticosteroid treatment, RANKL, which is released by osteoblasts, links with the RANK specific osteoclast receptor and stimulates osteoclastogenesis. This reaction can be blocked by osteoprotegerin, which is a competitive inhibitor to the same receptor site. A decreased osteoblast activity stimulates bone loss. The reduced level of osteocalcin, which is regarded as a marker for bone formation, and a simultaneously elevated RANK level reveal the promotion of osteoclast proliferation in patients treated with corticosteroids.